Exploring Blended Learning in the Humanities: A Pilot Study in a Graduate Course in Linguistics - Farias-Farias, M (Common Ground Research Networks, 2018)
Either for generational or disciplinary constraints, blended learning has made slow inroads in Chilean graduate programs in the humanities. We report on a pilot study that evaluates design and implementation of a graduate blended-learning course in linguistics. For baseline data, teachers and students were surveyed to assess use and access to internet technologies. Taking as main reference the concept of community of inquiry, we designed and piloted an elective course on brain and language, which was evaluated in terms of the teaching, cognitive, and social presences in a community of inquiry and by using a student survey questionnaire. Results from the first survey show that most teachers are familiar with Moodle and that both groups make massive use of email. WhatsApp and blogs are seldom used, and massive open online courses (MOOCs) are unknown. The course evaluation evidenced tensions among the three presences, probably attributed to the pedagogic culture in the humanities. Students, although appreciative of the blended learning modality that allowed them constant access to the course and more comfortable studying timing, also value face-to-face sessions. Implications for blended learning and online courses in graduate programs are discussed in the context of traditional instructional pedagogies in the humanities. © Common Ground Research Networks, Miguel Farías, All rights reserved.